Isolados de Trichoderma spp. como agentes promotores de crescimento e indutores de resistência em citros - Macedo, Vanessa Marcele (2014)
The species of fungi belonging to the genus Trichoderma can be found in many environments, especially in the rhizosphere, as colonizers of roots and plant growth promoters, for their ability in facilitating the absorption of nutrients and protecting them against attack by pathogens. Thus, this study aimed to test isolates of Trichoderma spp. for application as growth promoting agents and inducers of resistance to Phytophthora nicotianae in citrus rootstocks. First, eighteen isolates of Trichoderma were tested in vitro for their ability in inhibiting mycelial growth of P. nicotianae, in terms of: production of volatiles or termostable antifungical substances and cell free compounds. The growth promotion test was done with three rootstocks: Sunki tangerine, Swingle citrumelo and Rangpur lime, whose height and number of leaves were measured at 30, 60, 90, 120, 150 and 180 days after treatment with the antagonistic; and in the end of the test, the measuring of dry weight for shoots and roots of plants was measured. The seeds of the rootstocks were treated with the Trichoderma spp isolates and, 180 days later, was tested their capacity of resistance induction through pathogen inoculation on stem, assessed by lesion length. The Phytophthora control assay was carried out by seeds microbiolization of tangerine Sunki and Rangpur lime. By the results, it was found that all Trichoderma spp. isolates provided more than 50% inhibition of the pathogen colony, however, no one produced volatile metabolites. Five isolates produced cell free metabolites and, only the ACB-38 produced termostable antifungal substances, capable of inhibiting the pathogen growth. Trichoderma spp. has the potential for rootstocks growth promoting and resistence inducing to P. nicotianae, but the responses vary according to the plant genotype and the type of isolate antagonist applied. Most isolates of Trichoderma spp. tested were able to control P. nicotianae in Sunki tangerine and Rangpur lime plants.